Application of polybenzimidazole as mechanochromic material
By using polybenzimidazole polymer as a force-discoloring material, the problem of poor heat resistance of force-discoloring polymers in the prior art under high temperature conditions is solved, and the force-discoloring with high thermal decomposition temperature and high mechanical properties is achieved Effect.
Patent Information
- Application Number
- CN202411060711.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-02
- Filing Date
- 2024-08-02
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-08-02
AI Technical Summary
Existing powerful discoloration polymer materials have poor heat resistance under high temperature conditions and cannot meet the needs of high temperature use.
Polybenzimidazole (PBI) polymer is used as a force-discoloring material. It has high thermal decomposition temperature and high mechanical properties, and can maintain force-discoloring properties under high temperature conditions.
Polybenzimidazole polymer maintains excellent thermal stability and high mechanical strength at high temperatures, broadening the application scenarios of force-induced chromic materials and achieving effective force-induced chromic performance under high temperature conditions.
Smart Images

Figure CN119431787A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of mechanochromic materials, and in particular to the application of polybenzimidazole as a mechanochromic material. Background Art
[0002] Mechanochromic materials refer to a type of material that changes its color, luminescence and other properties after being stimulated by external forces, such as grinding, stretching and pressing. Mechanochromic materials have broad application prospects in many fields such as mechanical sensing, secure communications, non-destructive testing of materials and human motion monitoring.
[0003] Among the existing mechanochromic materials, small molecules account for a large proportion, while polymers account for a small proportion. The characteristics of polymers such as processability and mechanical strength make their application range more extensive. Mechanochromic polymer materials usually add color-changing molecules to polymers through blending or chemical bonding. Reported polymer materials that incorporate color-changing groups through chemical bonds include polymers containing spiropyran, rhodamine, or diarylbenzofuranone structures, which usually have a low melting point or glass transition temperature, poor heat resistance, and cannot meet the needs of use under high temperature conditions. Summary of the invention
[0004] The object of the present invention is to provide a polymer material with mechanochromic properties, which has a high thermal decomposition temperature / thermal stability and high mechanical properties to meet the requirements of use under high temperature and / or high mechanical property conditions.
[0005] The inventors of the present invention unexpectedly found that polybenzimidazole polymers have mechanochromic properties by themselves, without the need to dope mechanochromic small molecules into the polymer or to connect mechanochromic groups to or on polymer molecular chains through chemical bonds or non-chemical bonds. More specifically, the inventors of the present invention unexpectedly found that the fluorescence emission peak of polybenzimidazole polymers significantly shifts under external force stimulation.
[0006] Therefore, the present invention provides the use of polybenzimidazole polymer as a mechanochromic material.
[0007] The polybenzimidazole polymer can be used as a mechanochromic material in applications such as mechanical sensing, communication, anti-counterfeiting, non-destructive testing of materials, motion detection and micro-flow monitoring.
[0008] The present invention provides the following beneficial effects:
[0009] (1) The present invention discovers that polybenzimidazole has mechanochromic properties, which broadens the application field of polybenzimidazole;
[0010] (2) The fluorescence emission peak of the mechanochromic materials in the prior art often undergoes a red shift after being stimulated by an external force, while some embodiments of the present invention provide polybenzimidazoles whose fluorescence emission peak undergoes a blue shift after being stimulated by an external force;
[0011] (3) Polybenzimidazole materials have excellent thermal stability and high mechanical strength, which broadens the application scenarios of mechanochromic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 are H NMR spectra of the polymer of Example 1 (PBI-1) and the polymer of Example 7 (PBI-7);
[0013] Figure 2 is a thermogravimetric analysis spectrum of the polymer (PBI-1) of Example 1;
[0014] Figure 3 is the fluorescence spectrum of the polymer (PBI-2) of Example 2 before and after grinding; and
[0015] Figure 4 It is the fluorescence spectrum of the polymer film product (PBI-9) of Example 9 before and after stretching. DETAILED DESCRIPTION
[0016] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0017] The first aspect of the present invention provides the use of polybenzimidazole as a mechanochromic material. The present application finds that polybenzimidazole has mechanochromic properties. In the present invention, the polybenzimidazole can be any polybenzimidazole polymer known in the prior art.
[0018] According to the present invention, in some embodiments, the polybenzimidazole contains a structural unit A, and the structural unit A has a structure shown in formula (1):
[0019]
[0020] wherein the X1 group is a connecting group provided by an aromatic compound containing 1 to 10 benzene rings; and the Y group is an aromatic compound containing 1 to 10 benzene rings, a heteroaromatic compound containing 1 to 10 heterocyclic rings, an aromatic compound containing 1 to 3 heterocyclic rings and 1 to 8 benzene rings, a C4-C 10A connecting group is provided by at least one compound selected from cycloalkane, C1-C8 alkane, C2-C8 olefin; wherein X1 and Y groups are independently present or absent at least one substituent selected from hydroxyl, amino, cyano, halogen, C1-C4 alkyl and C1-C4 haloalkyl. In some embodiments, the polybenzimidazole is composed of structural unit A.
[0021] According to the present invention, in some embodiments, the polybenzimidazole contains structural unit A and structural unit C, contains structural unit A and structural unit D, or contains structural unit A, structural unit B, structural unit C and structural unit D; wherein the structural unit A has a structure shown in formula (1), the structural unit B has a structure shown in formula (2), the structural unit C has a structure shown in formula (1-1), and the structural unit D has a structure shown in formula (2-2):
[0022]
[0023] wherein the X1 and X2 groups are each independently a linking group provided by an aromatic compound containing 1 to 10 benzene rings; and the Y and Z groups are each independently an aromatic compound containing 1 to 10 benzene rings, a heteroaromatic compound containing 1 to 10 heterocyclic rings, an aromatic compound containing 1 to 3 heterocyclic rings and 1 to 8 benzene rings, a C4-C 10 A connecting group provided by at least one compound selected from cycloalkane, C1-C8 alkane, C2-C8 olefin; wherein, X1, X2, Y and Z groups are independently present or absent at least one substituent selected from hydroxyl, amino, cyano, halogen, C1-C4 alkyl, C1-C4 haloalkyl. In some embodiments, the polybenzimidazole is composed of structural unit A and structural unit C. In some embodiments, the polybenzimidazole is composed of structural unit A and structural unit D. In some embodiments, the polybenzimidazole is composed of structural unit A, structural unit B, structural unit C and structural unit D.
[0024] According to the present invention, in some embodiments, the polybenzimidazole contains or consists of a structural unit A and an optional structural unit B, wherein the structural unit A has a structure represented by formula (1), and the structural unit B has a structure represented by formula (2);
[0025]
[0026] Wherein, the X1 and X2 groups are each independently a connecting group provided by an aromatic compound containing 1 to 10 benzene rings; the Y and Z groups are each independently an aromatic compound containing 1 to 10 benzene rings, a heteroaromatic compound containing 1 to 10 heterocyclic rings, an aromatic compound containing 1 to 3 heterocyclic rings and 1 to 8 benzene rings, a C4-C 10A connecting group is provided by at least one compound selected from cycloalkanes, C1-C8 alkanes, and C2-C8 olefins, and when the structural unit B is present, Y and Z are different; wherein the X1, X2, Y and / or Z groups are each independently present or absent at least one substituent selected from hydroxyl, amino, cyano, halogen, C1-C4 alkyl, C1-C4 haloalkyl.
[0027] In the present invention, those skilled in the art know the connection mode of X1 and X2 groups in formula (1) and formula (2).
[0028] For example, for formula (1) and formula (2), when the X1 and X2 groups are each independently a linking group provided by benzene, the structural formulas of formula (1) and formula (2) can be respectively That is, the benzene ring and the imidazole ring share two pairs of carbon atoms. Any two pairs of ortho-position carbon atoms on the benzene rings in the X1 and X2 groups participate in the formation of the imidazole ring, and the two pairs of ortho-position carbon atoms may come from the same benzene ring or from different benzene rings in multiple benzene rings. For example, when the X1 group is a linking group provided by biphenyl, each benzene ring of the biphenyl may provide a pair of carbon atoms to form an imidazole ring, or one benzene ring may provide two pairs of ortho-position carbon atoms to form an imidazole ring.
[0029] In the present invention, C4-C 10 The cycloalkane may be, for example, cyclobutane, cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane or cyclodecane.
[0030] In the present invention, C1-C8 alkane can be, for example, methane, ethane, n-propane, isopropane, butane, pentane, hexane, heptane or octane. In some embodiments, C1-C8 alkane can also be C1-C8 alkane substituted with one or more halogen atoms, wherein the halogen atom can be selected from fluorine atom, chlorine atom and bromine atom.
[0031] In the present invention, the C2-C8 olefin may be, for example, ethylene, propylene, butene, pentene, hexene, heptene or octene.
[0032] In the present invention, the halogen may be selected from, for example, fluorine, chlorine and bromine.
[0033] In the present invention, the C1-C4 alkyl group may be, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl.
[0034] In the present invention, the C1-C4 haloalkyl group may be, for example, a halomethyl group, a haloethyl group, a halopropyl group, a haloisopropyl group, a halobutyl group, a halosec-butyl group, a haloisobutyl group or a halotert-butyl group; and the halogen atom in the C1-C4 haloalkyl group may be, for example, selected from a fluorine atom, a chlorine atom and a bromine atom.
[0035] According to the present invention, preferably, in some embodiments, the X1 and X2 groups are each independently a linking group provided by at least one compound selected from benzene, biphenyl, terphenyl, bridged benzene, pterygene and condensed aromatic hydrocarbons containing 1 to 10 benzene rings; more preferably, the X1 and X2 groups are each independently a linking group provided by at least one compound selected from benzene, biphenyl, bridged benzene, pterygene and naphthalene; further preferably, the bridged benzene has a structure shown in formula (3), formula (4) or formula (5), wherein R1, R3 and R4 are each independently selected from oxygen atoms, sulfur atoms, carbonyl groups, sulfonyl groups, methylene groups and halogen-substituted methylene groups; and R2 is selected from heteroaromatic rings;
[0036]
[0037] In the present invention, the heteroaromatic ring-containing compound may be, for example, pyridine or pyrimidine.
[0038] In the present invention, the connection positions (indicated by "dashed lines") of the structures represented by formula (3), formula (4) and formula (5) can be as follows:
[0039]
[0040] In the present invention, the connection positions include but are not limited to the above-mentioned representations; for example, any two adjacent connection positions on the same benzene ring are feasible.
[0041] According to the present invention, preferably, in some embodiments, the X1 and X2 groups are each independently selected from the following linking groups:
[0042]
[0043]
[0044] wherein G is selected from a hydrogen atom, a methyl group and a trifluoromethoxy group; J is selected from an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, a methylene group and a methylene group substituted with a methyl group or a trifluoromethyl group; L is selected from a bromine atom, a phenyl group and a phenyl group substituted with a trifluoromethyl group; and R is selected from a hydrogen atom, a carboxyl group, a hydroxyl group and a trifluoromethyl group.
[0045] In some embodiments of the present invention, the connection positions in the X1 and X2 groups may include but are not limited to the following connection positions:
[0046]
[0047] According to the present invention, in some embodiments, the Y and Z groups are each independently benzene, a 5-6 membered nitrogen-containing heterocyclic compound, an aromatic compound containing 2-7 benzene rings, an aromatic compound containing 1-2 nitrogen-containing heterocyclic rings and 1-5 benzene rings, a C4-C 10The linking group is provided by a compound of at least one of a cycloalkane, a C1-C8 alkane, and a C2-C8 alkene.
[0048] According to the present invention, in some embodiments, the molar content ratio of the X2 and X1 groups can be 0-9999, preferably 0-99; for example, it can be 0, 0.001, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 99, 100, and the range composed of any two of the above points. In the present invention, unless otherwise specified, the content ratio of the X2 and X1 structural units or groups in the polybenzimidazole is calculated according to the feed amount.
[0049] According to the present invention, preferably, in some embodiments, the Y and Z groups may each independently be a linking group selected from the following:
[0050]
[0051] C1-C8 alkyl;
[0052] wherein M is selected from a hydrogen atom, a cyano group, a methyl group, a phenyl group, and a phenyl group substituted with a methyl group or a trifluoromethyl group; P is selected from an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, a cyclobutyl group, a halogen-substituted cyclobutyl group, a methylene group, and a halogen-substituted methylene group; Q is selected from a bromine atom, a phenyl group, and a trifluoromethyl-substituted phenyl group; and T is selected from a hydrogen atom and a methyl group.
[0053] In the present invention, the connection position of the Y and Z groups is not particularly limited and can be any position on the connection group. For example, when the Y and Z groups contain a cyclic structure, the connection position can be a carbon atom on the cyclic structure; when the Y and Z groups are C1-C8 chain alkyl groups, the connection position can be any carbon atom in the chain alkyl group. In the present invention, the connection position of the Y and Z groups can include but is not limited to the following connection positions:
[0054]
[0055] In some embodiments, the polybenzimidazole polymers of the present invention do not contain mechanochromic groups generally known in the art, including but not limited to mechanochromic groups derived from tetraphenylethylene, triarylamines, spiropyrans, rhodamines, coumarins, and the like.
[0056] In the present invention, there is no particular limitation on the molecular weight of the polybenzimidazole. For example, the molecular weight of the polybenzimidazole can be selected according to specific application requirements.
[0057] According to the present invention, in some embodiments, the intrinsic viscosity of the polybenzimidazole may be 0.15-3.0 dLg -1 ; For example, it can be 0.15dL g -1 , 0.2dL g -1 , 0.3dL g -1 , 0.4dL g -1 , 0.8dL g -1 , 1.2dL g -1 、1.6dLg -1 、1.7dL g -1 、1.8dL g -1 、1.9dL g -1 , 2dL g -1 , 2.1dL g -1 , 2.2dL g -1 , 2.3dL g -1 , 2.4dL g -1 , 2.5dL g -1 , 2.6dL g -1 , 2.7dL g -1 , 2.8dL g -1 、2.9dL g -1 、3.0dL g -1 And the range consisting of any two of the above points.
[0058] According to the present invention, in some embodiments, the molar content ratio of the Z and Y groups can be 0-9999, preferably 0-99; for example, it can be 0, 0.001, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 99, 100, and the range composed of any two of the above points. In the present invention, unless otherwise specified, the content ratio of the Y and Z structural units or groups in the polybenzimidazole is calculated according to the feed amount.
[0059] In some embodiments of the present invention, a polybenzimidazole is provided whose fluorescence emission peak blue-shifts after being stimulated by external force.
[0060] In some embodiments of the present invention, the polybenzimidazole is poly(2,5-benzimidazole). Polybenzimidazole is a polymer known in the art. The present invention can use polybenzimidazole polymers of various structures known in the art.
[0061] The preparation of polybenzimidazole is known in the art. Polybenzimidazole can be prepared using various preparation methods known in the art.
[0062] In some embodiments, the present invention also provides a method for preparing the polybenzimidazole of the first aspect, the method comprising reacting at least one compound having a structure represented by formula (6) with HOOC-Y-COOH and optionally HOOC-Z-COOH;
[0063]
[0064] The X group in formula (6) is the same as the X1 and / or X2 group in formula (1) and formula (2), and will not be described in detail here.
[0065] According to the preparation method of the present invention, preferably, in some embodiments, the compound having the structure shown in formula (6) is selected from at least one of the following compounds:
[0066]
[0067] Wherein, G is selected from hydrogen atom, methyl and trifluoromethoxy, i.e. -H, -CH3, -OCF3;
[0068] J is selected from oxygen atoms, sulfur atoms, carbonyl groups, sulfonyl groups, methylene groups and methylene groups substituted with methyl or trifluoromethyl groups, for example, -O-, -S-,
[0069] L is selected from bromine atoms, phenyl groups and trifluoromethyl-substituted phenyl groups, for example, -Br as well as
[0070] R is selected from the group consisting of a hydrogen atom, a carboxyl group, a hydroxyl group and a trifluoromethyl group, i.e., -H, -COOH, -OH, -CF3.
[0071] According to the preparation method of the present invention, preferably, in some embodiments, HOOC-Y-COOH and optional HOOC-Z-COOH are each independently selected from at least one of the following compounds:
[0072]
[0073]
[0074] Wherein, n = 1-8;
[0075] M is selected from hydrogen, cyano, methyl, phenyl and phenyl substituted with methyl or trifluoromethyl, for example, -H, - C N,
[0076] P is selected from oxygen atoms, sulfur atoms, carbonyl groups, sulfonyl groups, cyclobutyl groups, halogen-substituted cyclobutyl groups, methylene groups, and methyl or trifluoromethyl-substituted methylene groups, for example, -O-, -S-,
[0077] Q is selected from a bromine atom, a phenyl group and a trifluoromethyl-substituted phenyl group, such as -Br, as well as
[0078] T is selected from a hydrogen atom and a methyl group, ie, -H, -CH3.
[0079] According to the preparation method of the present invention, preferably, in some embodiments, the reaction is carried out in a solvent, more preferably, the solvent is a mixed solution of methanesulfonic acid / phosphorus pentoxide or polyphosphoric acid, further preferably a mixed solution of methanesulfonic acid / phosphorus pentoxide, the mass of phosphorus pentoxide is 2-10% of the mass of methanesulfonic acid. The concentration of mixed monomers in the reaction system can be 3wt%-20wt%. According to the preparation method of the present invention, preferably, in some embodiments, the ratio of the molar amount of the compound having the structure shown in formula (6) to the total molar amount of HOOC-Y-COOH and optional HOOC-Z-COOH is 1:0.6-2, preferably 1:0.8-1.2.
[0080] In some embodiments, 3,4-diaminobenzoic acid is used as a monomer to prepare poly(2,5-benzimidazole).
[0081] According to the preparation method of the present invention, preferably, in some embodiments, the reaction time can be 1-8 hours, preferably 3-5 hours. The reaction temperature can be 60-230° C., preferably 60-170° C., more preferably 100-150° C. The reaction pressure can be normal pressure. According to the preparation method of the present invention, preferably, in some embodiments, the ratio of the molar amount of the compound having the structure shown in formula (6) to the total molar amount of HOOC-Y-COOH and the optional HOOC-Z-COOH is 1:0.6-2; for example, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, and the range composed of any two of the above points; preferably 1:0.8-1.2; wherein the molar content ratio of the X2 to X1 group can be 0-9999, preferably 0-99, for example, can be 0, 0.001, 0.01, 0.02, 0.03, 0.0 4, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 99, 100, and ranges consisting of any two of the foregoing; the molar content ratio of the Z to Y groups is 0-9999, preferably 0-99, for example, 0, 0.001, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 1 0, 20, 30, 40, 50, 60, 70, 80, 90, 99, 100, and ranges consisting of any two of the above points.
[0082] In some embodiments, the polybenzimidazole of the present invention may have one of the structures shown below:
[0083]
[0084] In the structures shown above, for copolymers, the structures shown only indicate that the polymer chain segments contain the repeating structural units shown or the polymer chain segments consist of the repeating structural units shown, and do not indicate the distribution of the repeating structural units shown in the polymer chain.
[0085] The present invention finds that polybenzimidazole has mechanochromic properties, that is, its fluorescence emission peak is significantly shifted (red-shifted or blue-shifted) under external force stimulation. The external force stimulation includes but is not limited to mechanical effects such as grinding, stretching, pressing, and impact. This discovery is unexpected because polymers with mechanochromic properties in the prior art either need to be doped with mechanochromic small molecules, or the mechanochromic groups need to be connected to the polymer molecular chain or to the polymer molecular chain through chemical bonds or non-chemical bonds.
[0086] In some embodiments, the present application provides the application of polybenzimidazole as a mechanochromic material, which may include the step of measuring the fluorescence emission spectrum of polybenzimidazole after the polybenzimidazole is subjected to an external force. Further, the application may also include the step of comparing the position of the fluorescence emission peak of the fluorescence emission spectrum of the polybenzimidazole measured after the external force is applied with the position of the fluorescence emission peak of the fluorescence emission spectrum of the polybenzimidazole before the external force is applied. The application may also send a warning signal based on the comparison result. For example, if the offset of the fluorescence emission peak of the fluorescence emission spectrum before and after the external force exceeds a set threshold value (for example, 3nm, 5nm or 10nm, etc.), a warning signal may be issued.
[0087] The present invention also provides the use of polybenzimidazole polymer as a mechanochromic material in mechanical sensing, communication, anti-counterfeiting, non-destructive material testing, motion detection, and micro-flow monitoring. Preferably, the application includes at least one of a stress sensor, anti-counterfeiting paper, color-changing textiles, a pressure sensor for a bandage during compression therapy, and a micro-flow monitor. In these applications, polybenzimidazole can, for example, change color in response to mechanical action, thereby providing useful information.
[0088] For example, polybenzimidazole can be coated or encapsulated on the inner surface of the microchannel; when the flow rate of the fluid inside the microchannel changes, the force on the polybenzimidazole changes, causing a change in the fluorescence emission peak, which can be captured by a detector connected to the microchannel, thereby realizing flow monitoring. For another example, a polybenzimidazole film can be set on the outside of a pipeline, and when the pipeline is deformed, the polybenzimidazole film is deformed, causing a change in the fluorescence emission peak, which can be captured by an external detector, thereby realizing an early warning of pipeline aging.
[0089] The present invention will be described in detail below through examples.
[0090] In the following examples,
[0091] The polymer yield was calculated according to the following formula:
[0092] Yield = actual polymer yield ÷ theoretical polymer yield × 100%;
[0093] The theoretical yield of the polymer = the number of moles of the compound represented by formula (6) × the molar mass of the repeating unit in the polymer structure.
[0094] 3,3′,4,4′-Tetraaminobiphenyl: Sigma-Aldrich; purity: 98%;
[0095] 4,4′-Diphenyl ether dicarboxylic acid: J&K Technology; purity: 98%;
[0096] Isophthalic acid: J&K Technology, purity 98%;
[0097] Terephthalic acid: J&K Technology, purity 98%;
[0098] 4,6-pyrimidinedicarboxylic acid: J&K Technology, purity 98%;
[0099] 2,5-Dihydroxyterephthalic acid: J&K Technology, purity 98%;
[0100] 3,5-Pyridinedicarboxylic acid: J&K Technology, purity 98%;
[0101] 5-aminoisophthalic acid: J&K Technology, purity 98%;
[0102] 1-Methylbenzimidazole: Inokai Technology, purity 98%;
[0103] 2-Hydroxybenzimidazole: Inotech Technology, purity 98%.
[0104] Example 1
[0105] A mixed monomer of 3,3',4,4'-tetraaminobiphenyl (2.14g) and 4,4'-diphenyl ether dicarboxylic acid (2.79g) in a molar ratio of 1:1.08 was added to a methanesulfonic acid / phosphorus pentoxide solution (solvent 44g) to form a reaction system, and the reaction was carried out at 150°C for 3h to obtain a reaction solution, and the reaction solution was introduced into water to precipitate the polymer, and then neutralized (sodium bicarbonate) and filtered to obtain the polymer PBI-1. Among them, the weight ratio of methanesulfonic acid to phosphorus pentoxide in the methanesulfonic acid / phosphorus pentoxide solution is 20:1, and the concentration of the mixed monomer in the reaction system is 10wt%. The yield of polymer PBI-1 is 99%. The nuclear magnetic hydrogen spectrum of PBI-1 was measured in Test Example 6. Figure 1 Its structure was confirmed by H NMR spectrum.
[0106] Example 2
[0107] The method of Example 1 was followed, except that 4,4′-diphenyl ether dicarboxylic acid was replaced with an equal molar amount of terephthalic acid, and the reaction time was 4 h. The yield of polymer PBI-2 was 99%, and its structure was confirmed by H NMR spectrum.
[0108] Example 3
[0109] A mixed monomer of 3,3',4,4'-tetraaminobiphenyl (2.14g), isophthalic acid (1.57g), and 4,6-pyrimidinedicarboxylic acid (0.18g) in a molar ratio of 1:0.945:0.105 was added to a methanesulfonic acid / phosphorus pentoxide solution (solvent 35g) to form a reaction system, and the reaction was carried out at 150°C for 3h to obtain a reaction solution, which was introduced into water to precipitate the polymer, and then neutralized (sodium bicarbonate) and filtered to obtain the polymer PBI-3. Among them, the weight ratio of methanesulfonic acid to phosphorus pentoxide in the methanesulfonic acid / phosphorus pentoxide solution was 20:1, and the concentration of the mixed monomer in the reaction system was 10wt%. The yield of polymer PBI-3 was 99%. Its structure was confirmed by nuclear magnetic hydrogen spectrum.
[0110] Example 4
[0111] The method of Example 3 was followed, except that 4,6-pyrimidinedicarboxylic acid was replaced with an equal molar amount of 2,5-dihydroxyterephthalic acid, and the reaction time was 4 h. The yield of polymer PBI-4 was 99%, and its structure was confirmed by H NMR spectrum.
[0112] Example 5
[0113] The method of Example 3 was followed, except that 4,6-pyrimidinedicarboxylic acid was replaced by an equal molar amount of 3,5-pyridinedicarboxylic acid, and the reaction time was 5 h. The yield of polymer PBI-5 was 99%, and its structure was confirmed by H NMR spectrum.
[0114] Example 6
[0115] The method of Example 3 was followed, except that 4,6-pyrimidinedicarboxylic acid was replaced by an equal molar amount of 5-aminoisophthalic acid, and the reaction time was 4 h. The yield of polymer PBI-6 was 99%, and its structure was confirmed by H NMR spectrum.
[0116] Example 7
[0117] A mixed monomer of 3,3′,4,4′-tetraaminobiphenyl (2.14 g), 4,4′-diphenyl ether dicarboxylic acid (2.44 g), and 5-aminoisophthalic acid (0.19 g) in a molar ratio of 1:0.945:0.105 was added to a methanesulfonic acid / phosphorus pentoxide solution (solvent 43 g) to form a reaction system, and the reaction was carried out at 150°C for 3 hours to obtain a reaction solution, and the reaction solution was introduced into water to precipitate the polymer, and then neutralized (sodium bicarbonate) and filtered to obtain the polymer PBI-7. Among them, the weight ratio of methanesulfonic acid to phosphorus pentoxide in the methanesulfonic acid / phosphorus pentoxide solution is 20:1, and the concentration of the mixed monomer in the reaction system is 10wt%. The yield of polymer PBI-7 is 99%. The nuclear magnetic hydrogen spectrum of PBI-7 was measured in Test Example 6. Figure 1 Its structure was confirmed by H NMR spectrum.
[0118] Example 8
[0119] The method of Example 7 was followed, except that the molar ratio was changed to 1:0.714:0.306 and the reaction time was 8 h. The yield of polymer PBI-8 was 99%. Its structure was confirmed by H-NMR spectrum.
[0120] Example 9
[0121] The method of Example 1 was followed, except that 4,4′-diphenyl ether dicarboxylic acid was replaced with an equal molar amount of isophthalic acid, and the reaction time was 5 h. The yield of polymer PBI-9 was 99%, and its structure was confirmed by H NMR spectrum.
[0122] PBI-9 was dissolved in DMSO solvent (concentration of 4 wt%), cast on a flat glass, placed in an oven at 80° C. for 10 h, and then taken out to obtain a PBI-9 membrane product, which was marked as PBI-9.
[0123] Example 10
[0124] The PBI membrane products were purchased from FuMA-Tech in Germany and were labeled as PBI-10.
[0125] Embodiment 11
[0126] The PBI membrane products were purchased from BASF in Germany and were labeled as PBI-11.
[0127] Test Example 1
[0128] The polymers (powders) prepared in Examples 1-8 above were tested for their mechanochromic properties.
[0129] Test method: Place the polymer powder in a solid fixture (two transparent quartz plates, one of which has a groove for placing the sample), and place it in a fluorescence instrument (Edinburgh-steady-state / transient fluorescence spectrometer FLS1000) to detect the fluorescence emission spectrum. Then, grind the polymer powder manually in a mortar for 30 seconds and place it in a solid fixture, and then place it in the fluorescence instrument again to detect the fluorescence emission spectrum. The displacement of the strongest fluorescence emission peak before and after grinding the polymer powder is shown in Table 1.
[0130] Test Example 2
[0131] The polymer films of Examples 9-11 were tested for their mechanochromic properties.
[0132] Test method for mechanochromic performance of polymer film: Place the film in a solid fixture and put it into a fluorescence instrument (Edinburgh-steady-state / transient fluorescence spectrometer FLS1000) to detect the fluorescence emission spectrum. Clamp both ends of the film with tweezers, stretch it for 30s without breaking it, and then place it in a solid fixture, and then put it into the fluorescence instrument again to detect the fluorescence emission spectrum. The film thickness is 40±5μm. The displacement of the strongest fluorescence emission peak before and after stretching the polymer film is shown in Table 1.
[0133] Table 1
[0134]
[0135] Note: “#” indicates the emission peak is blue-shifted; “*” indicates the emission peak is red-shifted.
[0136] Test Example 3
[0137] The thermal stability of the polymers prepared in the above examples was tested.
[0138] Thermogravimetric analysis test method: The test was conducted in a nitrogen atmosphere using a Q500 thermogravimetric analyzer from TA, USA. The heating rate was 10°C / min and the temperature range was 25-700°C. The thermal decomposition temperature of the polymer was T d5 % (temperature at which weight loss is 5% by mass) is shown in Table 2.
[0139] Table 2
[0140]
[0141] Test Example 4
[0142] The intrinsic viscosity of the polymers prepared in the above examples was tested.
[0143] Intrinsic viscosity test method: PBI is dissolved in concentrated sulfuric acid to prepare a sulfuric acid solution with a concentration of 0.6g dL-1. The sulfuric acid solution is added to the Ubbelohde viscometer and placed in a 25°C constant temperature water bath for 30 minutes. The outflow time of the solution is measured. Each sample is measured three times, and the time difference does not exceed 1s. The average value is recorded as t1, and the outflow time of concentrated sulfuric acid is recorded as t0. The intrinsic viscosity [η] of PBI is calculated as follows: Intrinsic viscosity Wherein, C is the concentration of PBI sulfuric acid solution. The test results are shown in Table 3.
[0144] Table 3
[0145]
[0146] Test Example 5
[0147] The mechanical strength of the film prepared in Example 9 was tested.
[0148] Mechanical testing method: The 5965 universal tensile testing instrument from Instron of the United States was used, the tensile rate was 1 mm / min, and the test temperature was 25°C.
[0149] The modulus of the PBI-9 membrane is 2.5 GPa, and the nominal modulus of the purchased PBI-10 is 4.5 GPa, both of which show excellent mechanical properties.
[0150] Test Example 6
[0151] The polymers of the examples were tested by hydrogen NMR spectra.
[0152] H NMR spectrum test method: Agilent 400-MR DD2 NMR spectrometer was used with a frequency of 400 MHz, tetramethylsilane (TMS) as the internal standard, DMSO-d6 as the solvent, and a test temperature of 40°C.
[0153] The H NMR spectra of the polymers of Example 1 and Example 7 are as follows: Figure 1 As shown, the proton signal at the chemical shift of 13.0 ppm in the spectrum can be attributed to the characteristic peak of active hydrogen in the PBI structural unit, the proton signals at 7.30 ppm and 8.28 ppm can be attributed to the characteristic peaks of the corresponding structural units after the polymerization of 4,4′-diphenyl ether dicarboxylic acid monomer, and the proton signals at 7.55-8.02 ppm can be attributed to the characteristic peaks of the corresponding structural units after the polymerization of tetraamine monomer and 5-aminoisophthalic acid monomer.
[0154] The results of H-NMR spectrum showed that polymers PBI-1 to PBI-9 were successfully obtained.
[0155] Comparative Example
[0156] The mechanochromic properties of 1-methylbenzimidazole and 2-hydroxybenzimidazole were tested respectively according to the method of Test Example 1. The test results showed that after grinding, the strongest fluorescence emission peaks of the two did not change, that is, they did not show mechanochromic properties.
[0157] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. Application of polybenzimidazole as mechanochromic material.
2. The use according to claim 1, wherein: The polybenzimidazole contains a structural unit A, and the structural unit A has a structure shown in formula (1): wherein the X1 group is a connecting group provided by an aromatic compound containing 1 to 10 benzene rings; and the Y group is an aromatic compound containing 1 to 10 benzene rings, a heteroaromatic compound containing 1 to 10 heterocyclic rings, an aromatic compound containing 1 to 3 heterocyclic rings and 1 to 8 benzene rings, a C4-C 10 A connecting group is provided by at least one compound selected from cycloalkanes, C1-C8 alkanes, and C2-C8 olefins; wherein the X1 and Y groups each independently contain or do not contain at least one substituent selected from hydroxyl, amino, cyano, halogen, C1-C4 alkyl, and C1-C4 haloalkyl.
3. The use according to claim 1 or 2, wherein: The polybenzimidazole contains structural unit A and structural unit C, structural unit A and structural unit D, or structural unit A, structural unit B, structural unit C and structural unit D; The structural unit A has a structure shown in formula (1), the structural unit B has a structure shown in formula (2), the structural unit C has a structure shown in formula (1-1), and the structural unit D has a structure shown in formula (2-2): Wherein, the X1 and X2 groups are each independently a connecting group provided by an aromatic compound containing 1 to 10 benzene rings; the Y and Z groups are each independently an aromatic compound containing 1 to 10 benzene rings, a heteroaromatic compound containing 1 to 10 heterocyclic rings, an aromatic compound containing 1 to 3 heterocyclic rings and 1 to 8 benzene rings, a C4-C 10 A connecting group is provided by at least one compound selected from cycloalkanes, C1-C8 alkanes, and C2-C8 olefins; wherein the X1, X2, Y, and Z groups each independently contain or do not contain at least one substituent selected from hydroxyl, amino, cyano, halogen, C1-C4 alkyl, and C1-C4 haloalkyl.
4. The use according to claim 1 or 2, wherein: The polybenzimidazole contains a structural unit A and an optional structural unit B, wherein the structural unit A has a structure represented by formula (1), and the structural unit B has a structure represented by formula (2); Wherein, the X1 and X2 groups are each independently a connecting group provided by an aromatic compound containing 1 to 10 benzene rings; the Y and Z groups are each independently an aromatic compound containing 1 to 10 benzene rings, a heteroaromatic compound containing 1 to 10 heterocyclic rings, an aromatic compound containing 1 to 3 heterocyclic rings and 1 to 8 benzene rings, a C4-C 10 A connecting group is provided by at least one compound selected from cycloalkanes, C1-C8 alkanes, and C2-C8 olefins, and when the structural unit B is present, Y and Z are different; wherein, at least one substituent selected from hydroxyl, amino, cyano, halogen, C1-C4 alkyl, C1-C4 haloalkyl is present or absent on the X1, X2, Y and / or Z groups independently.
5. The use according to any one of claims 2 to 4, wherein: The X1 and X2 groups are each independently a linking group provided by at least one compound selected from benzene, biphenyl, terphenyl, bridged benzene, pterygene and condensed aromatic hydrocarbons containing 1 to 10 benzene rings; preferably, the X1 and X2 groups are each independently a linking group provided by at least one compound selected from benzene, biphenyl, bridged benzene, pterygene and naphthalene; more preferably, the bridged benzene has a structure shown in formula (3), formula (4) or formula (5), wherein R1, R3 and R4 are each independently selected from oxygen atoms, sulfur atoms, carbonyl groups, sulfonyl groups, methylene groups and halogen-substituted methylene groups; and R2 is selected from heteroaromatic rings; Further preferably, the X1 and X2 groups are each independently selected from the following linking groups: wherein G is selected from a hydrogen atom, a methyl group and a trifluoromethoxy group; J is selected from an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, a methylene group and a methylene group substituted with a methyl group or a trifluoromethyl group; L is selected from a bromine atom, a phenyl group and a phenyl group substituted with a trifluoromethyl group; and R is selected from a hydrogen atom, a carboxyl group, a hydroxyl group and a trifluoromethyl group.
6. The use according to any one of claims 2 to 5, wherein: The Y and Z groups are each independently benzene, a 5-6 membered nitrogen-containing heterocyclic compound, an aromatic compound containing 2-7 benzene rings, an aromatic compound containing 1-2 nitrogen-containing heterocyclic rings and 1-5 benzene rings, a C4-C 10 A linking group provided by a compound of at least one of cycloalkane, C1-C8 alkane and C2-C8 alkene; Preferably, the Y and Z groups are each independently a linking group selected from the following: C1-C8 alkyl; wherein M is selected from a hydrogen atom, a cyano group, a methyl group, a phenyl group, and a phenyl group substituted with a methyl group or a trifluoromethyl group; P is selected from an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, a cyclobutyl group, a cyclobutyl group substituted with a halogen group, a methylene group, and a methylene group substituted with a halogen group; Q is selected from a bromine atom, a phenyl group, and a phenyl group substituted with a trifluoromethyl group; and T is selected from a hydrogen atom and a methyl group.
7. The use according to claim 1, wherein the polybenzimidazole is poly (2,5-benzimidazole).
8. The use according to any one of claims 1 to 7, wherein: The intrinsic viscosity of the polybenzimidazole is 0.15-3.0 dL g -1 and / or, The molar content ratio of X2 to X1 groups in the polybenzimidazole is 0-9999, preferably 0-99; and / or, The molar content ratio of the Z and Y groups in the polybenzimidazole is 0-9999, preferably 0-99.
9. The use according to any one of claims 1-8, wherein the polybenzimidazole is used as a mechanochromic material in mechanical sensing, communication, anti-counterfeiting, non-destructive material testing, motion detection, and micro-flow monitoring; preferably, it is used in stress sensors, anti-counterfeiting paper, color-changing textiles, pressure sensors for bandages during compression therapy, and micro-flow monitors.
10. The use according to any one of claims 1 to 9, wherein the fluorescence emission peak of the polybenzimidazole blue-shifts after being stimulated by external force.
Citation Information
Patent Citations
Mechanochromic material and preparation method thereof
CN109053779A
Self-reinforced mechanochromic material and preparation method thereof
CN112430306A
Fluorescent material and application thereof
CN114315732A
Metal complex with forward and reverse photochromic characteristics, preparation method and application of metal complex in information encryption
CN115975207A
Electrochromic glass component
CN1326561A